Dynamics of Treatment Supporters and Patients Starting HIV Therapy in Lima, Peru. (4th February 2019) - Harishankar, Krupa; Wong, Milagros; Saldana, Olga; Santa Cruz, Janeth; Lecca, Leonid; Munoz, Maribel; Nelson, Adrianne Katrina; Castro, Arachu; Shin, Sonya
As per the National HIV Program in Peru, the designation of a patient-elected treatment supporter is a requisite for starting antiretroviral therapy (ART). These individuals are expected to aid the patient in medical and social support. This qualitative study examines the interaction between treatment supporters and people living with HIV/AIDS (PLWHA) to elucidate key dynamics contributing to care. Twenty individual interviews with treatment supporters were analyzed alongside 5 group interviews: 2 groups of treatment supporters, 2 groups of PLWHA, and 1 group of community health workers. Findings characterized formal means of treatment support and informal emotional and instrumental support. Gradual transfer of treatment responsibilities from supporters to PLWHA was found to foster a sense of self-efficacy among PLWHA, and when paired with open communication and committed emotional support, created an ideal reciprocal relationship. However, lack of HIV-related knowledge among treatment supporters was detrimental. More training and systemic support for treatment supporters may optimize their role as informed participants in the care of PLWHA.